TUGAS DAN WEWENANG DIREKTORAN POLISI PERAIRAN KEPOLISIAN DAERAH KALIMANTAN TIMUR DALAM MENGAMANKAN DAN MEWUJUDKAN KETERTIBAN UMUM BERDASARKAN UNDANG – UNDANG TAHUN 2002 - SUNGGUH, ANDY ANA PUTRA (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSSTRACT       The high flow of traffic in East Kalimantan, both for trade and as a means of transformation and sailing did not go smoothly. The State Police of the Republic of Indonesia is a state instrument that provides services for the maintenance of security within the state including the maintenance and public order, law enforcement, protection, shelter and service to the community. One of them is the directorate of aquatic police under the Chief of Police in charge of carrying out the function of the police patrolling the waters and the handling of the criminal acts of the waters.       This study aims to determine the description of the role and execution of duties and authority of the police directorate of aquatic police of East Kalimantan Police in securing and realizing public order in the territorial waters of East Kalimantan.       The activities of the police directorate of aquatic police of East Kalimantan besides as a safeguard in the community also play a role in maintaining order and stability of community life. Community guidance conducted by the police directorate of aquatic police of East Kalimantan, by providing counseling and guidance to the community.       Directorate of aquatic police, abbreviated as directorate of aquatic police, is domiciled as the main implementing element of the police which is in charge of covering patrol including first handling of crime and livelihood as well as rescue accident in waters area and coastal community development.  Keywords: Duties and authority, position, police function.